2013
DOI: 10.1371/journal.pone.0080661
|View full text |Cite|
|
Sign up to set email alerts
|

Predicting Survival after Liver Transplantation Based on Pre-Transplant MELD Score: a Systematic Review of the Literature

Abstract: The model for end-stage liver disease (MELD) score is used to stratify candidates for liver transplantation based on objective measures of disease severity. MELD has been validated as a predictor of wait-list mortality in transplantation candidates and has been postulated as a predictor of post-transplant survival. The purpose of this study was to examine the predictive value of the pre-transplantation MELD score on post-transplant survival from relevant existing studies. A systematic review and critical appra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 9 publications
(11 reference statements)
5
66
1
1
Order By: Relevance
“…When stratifying patients in relation to MELD score (>25 and <25, respectively), there was also no difference in survival, either short-or long-term. In agreement with our data, a recent systematic review concluded that the use of pre-transplant MELD does not serve as a reliable predictor of posttransplantation survival [12]. In another paper, 145 LDLT were matched 1:1 with DDLT, and there was no difference in survival rates between the groups; they had 8 patients in each arm with MELD>25 [13].…”
Section: Discussionsupporting
confidence: 90%
“…When stratifying patients in relation to MELD score (>25 and <25, respectively), there was also no difference in survival, either short-or long-term. In agreement with our data, a recent systematic review concluded that the use of pre-transplant MELD does not serve as a reliable predictor of posttransplantation survival [12]. In another paper, 145 LDLT were matched 1:1 with DDLT, and there was no difference in survival rates between the groups; they had 8 patients in each arm with MELD>25 [13].…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have evaluated the ability of the MELD score to predict post-transplant mortality with mixed results 25 . In Europe, a number of previous studies demonstrated an increase in post-transplant mortality after adoption of the MELD-based allocation system – a change that closely correlated with transplanting candidates with higher MELD scores.…”
Section: Introductionmentioning
confidence: 99%
“…Debate, however, still exists about the pretransplant MELD score's capacity to predict posttransplant outcome (12), particularly because the MELD score was designed to predict pretransplant mortality. Although the MELD score may not be a good discriminator of outcome in the 21-34 range (13), it is clear that patients with MELD scores ≥35 have inferior patient and graft survival outcomes compared with those with a score of ≤20.…”
Section: Discussionmentioning
confidence: 99%